2020
DOI: 10.1016/j.crad.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on UK radiology training: a questionnaire study

Abstract: To understand the impact of COVID-19 on radiology trainee experience and well-being. MATERIALS AND METHODS: A questionnaire designed to capture the impact of COVID-19 on radiology training, working patterns, and well-being was sent to all speciality trainees in a regional UK radiology school. The survey was distributed at the beginning of May 2020 and responses collected over 2 weeks. Trainees were questioned about changes that had occurred over a time period starting at the beginning of the COVID-19 pandemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
3
17
1
Order By: Relevance
“…1 A singleregion trainee survey report performed in May 2020 found that all trainees reported a decrease in workload in response to COVID-19. 2 This resulted in a statistically significant drop in plain film reporting numbers and a selfreported drop in cross-sectional reports, ultrasound imaging and interventional procedures 2 ; this is congruent with the national activity data at the time of data collection. When surveyed by the General Medical Council (GMC) in late July/early August 2020; 61% of radiology trainees and trainers reported their workload was lighter.…”
Section: Imaging Workload and Workforcesupporting
confidence: 57%
“…1 A singleregion trainee survey report performed in May 2020 found that all trainees reported a decrease in workload in response to COVID-19. 2 This resulted in a statistically significant drop in plain film reporting numbers and a selfreported drop in cross-sectional reports, ultrasound imaging and interventional procedures 2 ; this is congruent with the national activity data at the time of data collection. When surveyed by the General Medical Council (GMC) in late July/early August 2020; 61% of radiology trainees and trainers reported their workload was lighter.…”
Section: Imaging Workload and Workforcesupporting
confidence: 57%
“…Many surveys have been published recently describing the effects of this pandemic which have concentrated on the training aspect of radiology and some analyzing the effect on the well-being of the radiologists who were working in a small group or regions. [ 2 , 3 ] Our survey reports the opinion of the radiologists working in different countries about their experience in this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Honoring resident vacation time should be prioritized in order to maintain resident well-being and prevent burn-out. Work by Veersauri and colleagues in the United Kingdom showed that nearly half of their study cohort, composed of radiology residents, reported worsened well-being compared to pre-pandemic ( 11 ). Similarly, Robbins et al found that the pandemic negatively impacted resident morale ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Solutions to decreases in imaging volumes ( 8 , 9 ) include dividing residents into two clinical groups with one reporting to service and the other assigned to distance learning, promoting online learning resources, assigning scientific/review articles with multiple choice questions, and hosting interesting case conferences ( 1 , 2 , 3 , 4 ). Additionally, studies have indicated that the pandemic has negatively impacted trainee well-being, including decreased resident morale ( 10 , 11 ). Promoting trainee wellness has been facilitated with the use of virtual strategies such as engagement in social media, encouraging resident meetings/huddles, hosting a virtual happy hour, and promoting institutional or other online well-being resources ( 2 , 3 , 4 , 10 ).…”
Section: Introductionmentioning
confidence: 99%